Little Quack - Thompson, Lauren; Anderson, Derek, 1969- (New York : Simon & Schuster Books for Young Readers, 2003)
One by one, four ducklings find the courage to jump into the pond and paddle with Mama Duck, until only Little Quack is left in the nest, trying to be brave.
Accelerated Reader AR
Keywords: Ducks -- Fiction; Animals -- Infancy -- Fiction; Courage -- Fiction